Pengaruh Kepuasan Kerja terhadap Kinerja Karyawan di RTO dengan Structural Equation Modeling (SEM) dan Partial Least Square (PLS) - Rosyadi, Imam; Adi Artanto, Fenilinas Adi; Febrianto, M Yusuf (Indonesian Journal of Strategic Management, 2021)
RTO Group is a company engaged in many fields, to improve the quality or performance of employees in the RTO Group, research is carried out with the aim of knowing what affects employee performance. By using the Job Description Index (JDI) method, employee performance will be influenced by job satisfaction, work motivation and organizational commitment. From the data that has been taken from the employees of the RTO Group, the data is estimated using the Structural Equation Modeling (SEM) and Partial Least Square (PLS) methods. By using SEM, structural equations will be built, and these equations will be estimated using PLS. The results obtained after the data were analyzed showed that job satisfaction influenced work motivation of 43.1%, work motivation had an effect on organizational commitment of 25.6%, organizational commitment had an influence on job satisfaction of 52.4%, job satisfaction, work motivation, and organizational commitment have an effect on employee performance by 78.7%. Meanwhile, in the significant test, all relationships between constructs are significant and have a positive relationship, only the relationship between work motivation and employee performance is not significant.